Impact of the change in the number of days of dust storms in the maritime activity of the Iraqi port of Khor Zubair for the period (2019-2008 (Journal of the College of Basic Education, 2022)
Going on the sea in the context of showing the effect of the number of days the survival of climatic phenomena such as storms, dust, dust and the dust rising in the Basra governorate of the state of climate (2019-2008) Whether it is the amount of direction change of the upward call of death or decline connect the negative impact on the province of Basra and its sea borders with the Arabian Gulf and its impact on the maritime activity at the port of Khor Al-Zubair show that dust storms and dust the dust spiraling effect is clear in the weather and climate of Iraq in general and the climate of the province of Basra, they are often lower temperature due to the Prevention of the arrival of solar radiation, the Earth and the lack of clarity and because of the stirring of dust and dirt and vision and a rise in the activity of air currents and the high number of days of survival may impact in the war of maritime trade at the port of Khor Al-Zubair, Iraq, as it was found that the number of dust storms and dust The escalating more frequent in the first methodology, either in the states of the region in the recent tell occurrence of such phenomena as the season (2018-2019) the number of dust storms (1) day, so it was a trade port active at (450) ship, or dust spiraling decoder number (60) days in the season (2010-2011) affect his role in the trade of the port as down the number of ships to the (72) ship The lowest season was in (2018-2019) and its number was (6) days, offset by the flourishing of the maritime trade movement so that the number of ships entering and leaving the port reached its highest rate of (450) ships. In the ports in general and the port of Khor Al Zubair in particular. , while decreased the number of days of dust the chilled (24) days in the season (2018-2019) Where flourished foreign trade at the port, at (450) ship because he wasn't studying the affect the war file within the Navy.